(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2007)
Change of heart rhythm variability at examinees with various initial degree of aggression and conflictness is researched at aggressive environment modeling with use of «aggressive» computer games. Authentic decrease of an anxiety level and stress index at teenagers with a high level of aggression and conflictness is revealed, and at teenagers with a low level – authentic changes is not observed. Beneficial effect of «aggressive» computer games on psychoemotional sphere of teenagers is revealed.